Successful Oral Levothyroxine Desensitization in a Patient with Severe Hypothyroidism Post Radioactive Iodine Therapy: A Case Report - Chua, Yi Jiang; Shing Shen, Bay; Yun, Taye Zhi; Singarayar, Carolina; Hui, Foo Siew (Journal of the ASEAN Federation of Endocrine Societies, 2022)
Levothyroxine remains the standard therapy for patients with hypothyroidism worldwide. Levothyroxine allergy is rarely seen and alternative therapies are less efficacious and scarcely available. The use of liothyronine (LT3) monotherapy is less favoured due to its short half-life and unpredictable pharmacological profile. We report a 59-year-old male with a hypersensitivity reaction to levothyroxine who was successfully desensitized with oral levothyroxine within a day using a 14-step protocol (Table 1.1).